G350 Outcome of narrow complex arrhythmias in infants: a six-year retrospective study. (7th April 2014) - Khushu, A; Kelsall, AW; Yates, R; Singh, Y
Abstract : Background: Supraventricular tachycardia (SVT) is the most common arrhythmia in infants with an incidence of 1/250001. Most of the infants with SVT are treated with maintenance anti-arrhythmic therapy for 612 months. Aim: To study the clinical presentation and outcome of narrow complex cardiac arrhythmias in infants. Methods: Patients were identified from the paediatric and neonatal databases and all infants diagnosed with narrow complex arrhythmias in children less than 1 year of age were included in the study. The data was collected from the electronic hospital records and case notes. Results: 35 infants diagnosed with narrow complex arrhythmias were identified. Nineteen (54%) infants presented within first 7 days after birth, 8 (23%) between 1–4 weeks and the remaining 8 (23%) presented after 4 weeks of age. Nine (26%) infants had underlying significant congenital heart disease including Ebstein anomaly (2), congenitally corrected TGA (1), TGA (1), hypoplastic arch and coarctation (2) and AVSD with right atrial isomerism (1). Only three (9%) infants had antenatal diagnoses of arrhythmia. SVT was diagnosed in 28 infants (80%). Other types of arrhythmias included atrial flutter (3), ectopic atrial tachycardia (3) and atrial tachycardia (1). Five infants were transferred to other hospitals and excluded from the study. 3 infants died of other underlying serious conditions. Eight patients (20%) did not require maintenance therapy including one case of atrial flutter needing DC cardioversion. Of the 19 infants diagnosed with narrow complex tachycardia needing maintenance therapy, 6 (32%) are still on maintenance therapy while in 13 (68%) infants maintenance therapy was stopped. Ten had no recurrences after stopping maintenance while three had recurrences needing re-starting treatment. The average duration of medical treatment was 8 months. Maintenance medications used included propranolol, flecainide and amiodarone. 63% cases (12) had monotherapy while 37% (7) multi-drug therapy. Conclusion: Narrow complex tachycardia carries good prognosis in infants without any underlying morbidities. About a quarter of patients had underlying congenital heart condition. About two thirds children are managed on single medication while the other third needed multi-drug therapy for an average duration of 8 months. Reference: Dubin AM. Arrhythmias in the Newborn. NeoReviews 2000;1:e146-151